Spatial Distribution and Morphology Character of Podang Mangoes (Mangifera indica L.) from Five Sub-district in Kediri Regency, East Java, Indonesia - Aisyah Hadi Ramadani; Muhammad Riza Firdausi; Rasyadan Taufiq Probojati; Ahmad Affan Ali Murtadlo (Biotropic : The Journal of Tropical Biology, 2020)
This study obejctives to determine the distribution maps and identify the morphological character of local Mangga Podang at five sub-districts in Kediri. This research used purposive sampling method for collecting data. Coordinate of local mango wasanalyzed using QGIS software version 3.6. Morphological characters are examined by observing the morphology. Microclimate factors that were measured are altitude, intensity, temperature and moisture of soil and air, soil pH, and soil nutrient. Morphological characterswere analyzed for homogenity by statistical test. The results showed that Mangga Podang distribution has spread in residential areas and has different altitude factors between 85-459 meters above sea level. The total population(individu/400m2) found in this study were Mojo10(11.2%), Banyakan 17 (19.1%), Grogol8 (9%), Semen 3 (3,4%)and Tarokan51 (57.3%). Mangga Podangof Kediri Regency generally have homogenous morphological characters, but there were the special character which differs each other, they are the number of flowers in 1 panicle, the weight of ripe fruit and exocarp color of ripe fruits. This morphological variation dependent to light intensity, altitudinal, the velocity of wind and soil nutrient factors.